Molecular Profile of a Pituitary Rhabdomyosarcoma Arising From a Pituitary Macroadenoma: A Case Report - Lu, Jinci; Chen, Liam (Frontiers in Endocrinology, 2021)
Pituitary sarcoma arising in association with pituitary adenoma is an uncommon finding. Most cases of secondary sarcoma have been noted to arise with a median interval of 10.5 years post radiation. In this case report, we describe a 77-year-old man with an incidental discovery of a pituitary macroadenoma on magnetic resonance imaging (MRI) and underwent radiotherapy. Three years after radiation treatment, there was an acute change in clinical symptoms and increase in tumor size and mass effect on the optic chiasm which prompted surgical resection. A pituitary adenoma along with a separate spindle-cell sarcomatous component was identified in histology. Immunohistochemical stain for muscle markers confirmed a development of pituitary rhabdomyosarcoma (RMS). Molecular profiling of the tumor identified mutations in TP53, ATRX, LZTR1, and NF1. Despite its rarity, characterization of pituitary RMS with immunohistochemistry and molecular studies may provide an insight to its pathophysiological relationship with pituitary adenoma.